Filantropi Islam Sebagai Media Peningkatan Kebahagiaan Muslim Indonesia - Setiawan, Wahyudi; Iman, Nurul (Proceedings of Annual Conference for Muslim Scholars, 2019)
This paper is a paper that uses the study of language and text as well as in presenting data, in this study the theme adopted is the Islamic Boarding School and Nature Conservation: Islamic Boarding School Reading With Hermeneutic Studies on Surat al-Baqarah verse 35 Related to Forest Conservation Protection in Indonesia. There are three important questions related to this study, first, how is the relationship (pesantren al-Quran) of the Koran with the Semsta or Nature Conservation? how is the Hermenutics Concept of Developing Ulumul Al-Quran in Indonesia and its Application in the Study of Reading the Al-Quran Text? the third is how the Reading of the Hermenutic Study of Surah Al-Baqarah verse 35 is related to the conservation of Protection Forest in Indonesia. The results of this paper are first, how the concept of Al-Quran and Nature Conservation, secondly, knowing the Hermeneutic concept of the Development of Ulumul al-Quran and its interpretation of the Al-Quran Text in Indonesia, and thirdly the reading of Hermeneutics of the Koran in Surah Al Baqarah verse 35 and engagement with a study of Conservation Forest Conservation in Indonesia